2020
DOI: 10.1371/journal.pntd.0008355
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya in Indonesia: Epidemiology and diagnostic challenges

Abstract: BackgroundChikungunya virus (CHIKV) is often overlooked as an etiology of fever in tropical and subtropical regions. Lack of diagnostic testing capacity in these areas combined with co-circulation of clinically similar pathogens such as dengue virus (DENV), hinders CHIKV diagnosis. To better address CHIKV in Indonesia, an improved understanding of epidemiology, clinical presentation, and diagnostic approaches is needed. Methodology/Principal findingsAcutely hospitalized febrile patients �1-year-old were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
1
19
1
3
Order By: Relevance
“…Overall, our study found that 2.4% (95% CI: 1.3-4.2%) of febrile patients across the three sites had previously been exposed to CHIKV. This is also relatively low in comparison to the results of a recent study of febrile patients in central Indonesia, which reported IgG seroprevalence rates ranging from 25.2-45.9% across 7 cities in Java, Bali and South Sulawesi [43]. High rates have also previously been reported for febrile patients from other countries in Asia, including the Philippines (57.5%), Vietnam (50.0%) and Sri Lanka (38.0%) [44].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Overall, our study found that 2.4% (95% CI: 1.3-4.2%) of febrile patients across the three sites had previously been exposed to CHIKV. This is also relatively low in comparison to the results of a recent study of febrile patients in central Indonesia, which reported IgG seroprevalence rates ranging from 25.2-45.9% across 7 cities in Java, Bali and South Sulawesi [43]. High rates have also previously been reported for febrile patients from other countries in Asia, including the Philippines (57.5%), Vietnam (50.0%) and Sri Lanka (38.0%) [44].…”
Section: Discussioncontrasting
confidence: 61%
“…The low seroprevalence observed in Ambon, Batam and Banjarmasin compared to cities in central Indonesia [43] may be due to an absence of recent outbreaks in the study regions. A similar regional difference has been reported from other Southeast Asian countries where the virus is endemic, including Thailand, where IgG seroprevalance was observed to be significantly lower in participants younger than 30 y.o.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…7 Ko-infeksi dan ko-sirkulasi antara virus Chikungunya dan Dengue juga terkadang dijumpai karena kesamaan dari vektornya. 6,8 Menurut penelitian Heath et al dan Chompoosri et al, virus Chikungunya juga dapat ditularkan dari nyamuk Ae. aegypti maupun Ae.…”
Section: Pendahuluanunclassified
“…1,5 Berbeda dengan Demam Berdarah Dengue (DBD) yang sudah dikenal luas, underdiagnosis chikungunya masih sering terjadi di Indonesia. 8 Hal tersebut disebabkan presentasi/gejala klinis chikungunya sulit dibedakan/tumpang tindih dengan demam berdarah dan infeksi penyakit endemik lainnya serta kurangnya kapasitas pengujian diagnostik. 3,8 Jumlah kasus chikungunya di Indonesia sebanyak 5.042 kasus pada tahun 2019.…”
Section: Pendahuluanunclassified